Chair side measuring instrument for quantification of the extent of a transverse maxillary occlusal plane cant - Farhad B. Naini; Ashraf Messiha; Daljit S. Gill (SpringerOpen, 2019)
Abstract Background Treatment planning the correction of a transverse maxillary occlusal plane cant often involves a degree of qualitative "eyeballing", with the attendant possibility of error in the estimated judgement. A simple chair side technique permits quantification of the extent of asymmetry and thereby quantitative measurements for the correction of the occlusal plane cant. Methods A measuring instrument may be constructed by soldering the edge of a stainless steel dental ruler at 90° to the flat surface of a similar ruler. With the patient either standing in natural head position, or alternatively seated upright in the dental chair, and a dental photographic retractor in situ, the flat under-surface of the horizontal part of this measuring instrument is placed on a unilateral segment of a bilateral structure, e.g. the higher maxillary canine orthodontic bracket hook. The vertical ruler is held next to the contralateral canine tooth, and the vertical distance measured directly from the canine bracket to the flat under-surface of the horizontal part of the measuring instrument. Results This vertical distance quantifies the overall extent of movement required to level the maxillary occlusal plane. Conclusions This measuring instrument and simple chair side technique helps to quantify the overall extent of surgical levelling required and may be a useful additional technique in our clinical diagnostic armamentarium.